Exploring post-discharge connection for HIV-infected patients in residential centers: perspectives from experts and patients - Abbas Boosiraz; Sepideh Alizadeh; Tayebeh Amiri; Zohreh Rostam Afshar; Maryam Sargolzayi Moghadam; Shahrzad Ghorbani; Nazanin Shahrokhnia; Sarina Borran; SeyedAhmad SeyedAlinaghi (فصلنامه ابن سینا)
Background and aims: Many clients referred to accommodation centers and camps are already undergoing antiretroviral treatment after being diagnosed with HIV. Discontinuation or irregular use of medication can lead to treatment failure and drug resistance. This study aimed to investigate the perspectives of experts, key stakeholders, and patients on all aspects of HIV diagnosis, care, and treatment, both within and outside residential facilities. Methods: A focus group discussion lasting an average of 75 minutes was held with 12 experts, and three patients were interviewed individually. This research took place at the Iranian Research Center for HIV/AIDS affiliated with Tehran University of Medical Sciences in September 2021. The analysis was conducted using content analysis, which involved categorizing data into main categories, sub-categories, and codes. Open code software was utilized for this purpose. Results: The study uncovered challenges faced by individuals before and after discharge from these facilities (important categories and sub-categories), including financial concerns, a shortage of specialized and knowledgeable staff, lack of understanding among clients regarding medication adherence and treatment benefits, inadequate attention given to clients, absence of follow-up contact information, substance abuse issues, and insufficient prioritization of HIV patients in these settings. Conclusion: The findings highlight the necessity for new strategies in post-discharge follow-up, as well as the provision of medical, supportive, and educational services. Potential solutions may include providing housing for homeless patients, assisting patients in accessing mental health counseling centers, optimizing existing resources, and fostering a community environment that actively fights against stigma and discrimination.